Activation of a cryptic 5' splice site by U1 snRNA. - Alvarez, C J (2001)
In the course of analyzing 5' splice site mutations in the second intron of Schizosaccharomyces pombe cdc2, we identified a cryptic 5' junction containing a nonconsensus nucleotide at position +2. An even more unusual feature of this cryptic 5' junction was its pattern of activation. By analyzing the profile of splicing products for an extensive series of cdc2 mutants in the presence and absence of compensatory U1 alleles, we have obtained evidence that the natural 5' splice site participates in activation of the cryptic 5' splice site, and that it does so via base pairing to U1 snRNA. Furthermore, the results of follow-up experiments strongly suggest that base pairing between U1 snRNA and the cryptic 5' junction itself plays a dominant role in its activation. Most remarkably, a mutant U1 can activate the cryptic 5' splice site even in the presence of a wild-type sequence at the natural 5' junction, providing unambiguous evidence that this snRNA redirects splicing via base pairing. Although previous work has demonstrated that U5 and U6 snRNAs can activate cryptic 5' splice sites through base pairing interactions, this is the first example in which U1 snRNA has been implicated in the final selection of a cryptic 5' junction.